EVALUASI EFEKTIFITAS VAKSINASI RABIES PRIMER PADA ANJING DI KECAMATAN MAGEPANDA KABUPATEN SIKKA - Yoseph Klaudius; Maria A.W. Gelolodo; Aji Winarso (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2020)
Rabies has been a serious public health threat in Flores Island, Indonesia since it was introduced by Buton Island fisherman in 1997. The first case of canine rabies was officially confirmed in 1998 in Tanjung Bunga, East Flores regency. The virus spread to other regencies in the island, including Sikka regency. To control the disease, a routine vaccination program has been applied since 2000, however, this program has not yet been successful in eliminating canine rabies from Flores. The aim of this study is to evaluate the effectiveness of canine rabies vaccination in Magepanda, Sikka. Total 32 dog’s serum samples with age range around 6-12 months were collected in the 14th day post rabies vaccination. Then, those serum samples were examined using ELISA test to measure its antibody titer. The test showed that 78,125% of the samples presented protective antibody titers. Chi-square analysis results show that, no significant relationship between age and the dog with the results of the rabies antibody titer (ELISA) in District Magepanda Sikka, it is probably caused by the uneven distribution of the dog's life.